Neurologic Changes With Aging, Physical Activity, and Sport Participation. Issue 1 (January 2016) - Leach, Susan Joy; Ruckert, Elizabeth Audrey
Abstract : The purpose of this review is to explore age-related changes within the neurologic system and examine the influence of physical activity and sport participation on those changes. Cognitive measures such as executive function, attentional resources, and information processing are used to study the neurologic system via brain technology and behavioral outcomes within the context of aging, physical activity, and sport participation. Studies suggest that sport participation in cycling, running, swimming, and tennis may have benefits for older adults in reaction time, attention, coordination, and accuracy during daily tasks.